2012 International Conference on Electromagnetics in Advanced Applications 2012
DOI: 10.1109/iceaa.2012.6328760
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of far field patterns for radio astronomy applications through the use of the Jacobi-Bessel series

Abstract: The Jacobi-Bessel (JB) series representation for modeling reflector antenna patterns is proposed to be used as a reference tool to assess and improve the pattern shape of multi-beam wide-scan radio telescopes. After expanding each beam in JB functions, the number of dominant JB functions per beam not only serves as an indication of the beam calibratability (beam smoothness), but is a measure for the uniformity of the scanned patterns as well (inter-beam comparison). It is demonstrated that the first term in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The reference pattern employed in [11] to constrain the main beam shape of a scanned reflector is based on the JB-series solution for modeling reflector antenna far field patterns. The first term in this series is the near-boresight approximation of the co-polarized far field pattern radiated by a circular aperture with a uniform amplitude and phase distribution [16], i.e.,…”
Section: Antenna Pattern Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The reference pattern employed in [11] to constrain the main beam shape of a scanned reflector is based on the JB-series solution for modeling reflector antenna far field patterns. The first term in this series is the near-boresight approximation of the co-polarized far field pattern radiated by a circular aperture with a uniform amplitude and phase distribution [16], i.e.,…”
Section: Antenna Pattern Modelmentioning
confidence: 99%
“…Previously, beamforming techniques have been used to create similarly shaped beams over the FoV by conforming them to an elliptical reference pattern, but at the cost of a significant loss in sensitivity [6] (up to 25%). An initial study has shown that this loss can be reduced by applying the same beamforming technique, but using a reference pattern that more closely matches the natural radiation characteristics of large aperture antennas [11]. Therein, the first term of the Jacobi-Bessel (JB) series solution of reflector antenna far field patterns [12], [13] was used as a reference pattern to define directional constraints in a Linearly Constrained Minimum Variance (LCMV) beamforming Phased Array Feed (PAF).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation